Evaluation of inflammatory and hematological parameters in patients diagnosed with COVID-19 - Çiğdem Mermutluoğlu; Recep Dursun; Fesih Aktar; Saim Dayan; Mustafa Kemal Çelen; Ali Kemal Kadiroğlu; Erdal İnci; Rengin Karagöz; Mahir Kuyumcu; Nida Özcan; Recep Tekin (Journal of Infection in Developing Countries)
Introduction: This study aims to research the effects of hematological and inflammatory parameters on the prognosis of COVID-19 disease and hospitalization duration.